Cooling effectiveness enhancement of parallel air-cooled battery system through integration with multi-phase change materials - Mohammed A.G.; Hasini H.; Elfeky K.E.; Wang Q.; Hajara M.A.; Om N.I. (Elsevier Masson s.r.l., 2025)
This work presents a numerical investigation of the integration of conventional parallel air-cooling battery system with multi-phase change materials (PCMs) to improve the cooling effectiveness at low power consumption (Pc) rate. The study considers various cells partitioning of the PCMs on nine different parallel air-cooled battery packs. The impact of PCMs pattern schemes, inclination angle of the manifold, and air inlet velocity are analysed by employing finite volume technique coupled with an enthalpy-porosity method. Compared with a typical parallel air-cooling system, despite 90% reduction in the air inlet velocity, the integrated system successfully lowers the maximum temperature (Tmax) by 12.0 K and improves uniformity of temperature distribution based on standard deviation (SDV) of temperature field by 43.9%. Subsequently, inclining the air inlet manifold to an angle close to vertical leads to a poor cooling performance. Also, a proper pattern of PCMs cells partitioning having a trapezoidal cell shape at the top and bottom, and a parallelogram cell shape at the midsection exhibits a better heat dissipation performance. Moreover, compared to the module with highest inlet velocity of 1.5 m/s, reducing the inlet velocity by 66.7% still controls Tmax at 313.13 K which is well below the critical limit, and decreases the Pc by 65.8%. ? 2024 Elsevier Masson SAS